In Sickness and in Health: Risk-Sharing Within Households in Rural Ethiopia - Dercon, Stefan; Krishnan, Pramila (University of Oxford: Centre for the Study of African Economies (CSAE), 1997)
Households in rural Ethiopia, like farm households elsewhere in developing countries, live in a highly risky and volatile environment and suffer tremendous variation in incomes, mainly due to factors beyond their control. While the paper investigates whether households act as risk-sharing institutions so that nutritional levels are smooth across members of the households, it also looks at the factors determining the intra-household allocation of nutrition. The paper further examines whether, in the face of fluctuating incomes, the burden of adjustment is borne by women, particularly in poorer households. Panel data from Ethiopia is used to ask whether women in poor households are likely to experience more fluctuations in their nutritional status and consumption than men.
Includes bibliographical references: p. [37]-44.
ne 22/03/2018
Loan
Keywords: Medicine and Arts; Arts and Society